La València del vuit-cents a través del dietari d'Ignacio Gilabert Soler (1744-1751). - SOLER, GABRIELA (Scripta)
This article aims to analyze an exceptional egodocument for the Valencian territory, the diary of Ignacio Gilabert Soler written between 1744 and 1751 and currently held in private hands. The author of the diary belongs to the intermediate groups of Valencian society of the time. Its content reflects the expenses and management of the family's household, providing insight into the everyday life, family life, and intimacy of the author and his environment. This allows us to understand the social dynamics of these intermediate groups, which have sometimes been marginalized by traditional history. Through the analysis of this source, we have been able to learn about the socio-cultural and economic transformations of Valencia at the time, which heralded the advent of the new bourgeois society.